Adverse effects of linoleic acid: Influence of lipid oxidation on lymphatic transport of citrus flavonoid and enterocyte morphology. (1st February 2022) - Yao, Mingfei; Kitamura, Fuki; Han, Yanhui; Du, Hengjun; Julian McClements, David; Xiao, Hang
Graphical abstract: Highlights: LA improved the absorption of 5-DMT by stimulating production of lipid droplets and chylomicron. The amount of 5-DMT transported to the bacterial side also enhanced by oxidized LA. Oxidized LA induced ROS, affected tight junction and caused damages to Caco-2 monolayer. Abstract: Lipids usually contain a large ratio of polyunsaturated fatty acids (PUFAs), which are highly susceptible to oxidation. Presence of oxidized lipids in foods may affect the bioavailability of lipophilic bioactive components after ingestion. In this study, the effect of oxidized and unoxidized linoleic acid (LA) on the transport of a highly lipophilic bioactive citrus flavonoid (5-hydroxy – 6, 7, 8, 4′ tetramethoxylflavone or 5-DMT) was determined using a Caco-2 cell model. Results demonstrated that compared to free 5-DMT, unoxidized LA improved the trans-enterocyte absorption of 5-DMT by stimulating the production of lipid droplets and chylomicrons. Although the amount of 5-DMT transported across the enterocyte doubled by oxidized LA compared to free 5-DMT, it significantly induced reactive oxygen species (ROS), affected the function of tight junction and caused damages to the morphology of enterocyte monolayer. This study re-emphasized the importance of preventing lipid oxidation in foods.